Break-down of the magnetically insulated diode - Zagrebelnyy, I.A.; Zykov, A.V.; Glaznev, M.V. (Вопросы атомной науки и техники, 2007)
In the present work the comparative analysis of computer simulation results and experimental data for “Radical” ion source is carried out. The break-down curves are presented for different boundary conditions, such as: cathode-sheath-anode, plasma-sheath-anode, ion-beam plasma-sheath-anode. The influence of thermo-electron emission on the discharge characteristic was also investigated. Представлено порівняльний аналіз чисельних розрахунків й експериментальних даних для іонного джерела іонів “Радикал”. Розрядні криві представлені для різних типів граничних умов таких як: катод-шар-анод, плазма-шар-анод, іонно-пучкова плазма-шар-анод. Також досліджено вплив термоелектронної емісії на розрядні характеристики. Представлен сравнительный анализ численных расчетов и экспериментальных данных для ионного источника ионов “Радикал”. Разрядные кривые представлены для различных типов граничных условий таких как: катод-слой-анод, плазма-слой-анод, ионно-пучковая плазма-слой-анод. Также исследовано влияние термоэлектронной эмиссии на разрядные характеристики